1988
DOI: 10.1063/1.100010
|View full text |Cite
|
Sign up to set email alerts
|

Supermode control in diffraction-coupled semiconductor laser arrays

Abstract: Supermode control is demonstrated theoretically and experimentally in diffraction-coupled semiconductor laser arrays. A linear theory is presented to determine the supermode threshold gain as a function of the coupling cavity length. By fabricating devices with different coupling cavity lengths, array operation in both the fundamental and highest order supermodes is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In one depiction [9], the array of coupled lasers is treated as a single compound-cavity laser. The intrinsic laser dynamics are ignored and coherent beam combination is discussed in terms of the static eigenmodes, often referred to as supermodes, of the compound-cavity setup [18]. Although an analysis of these solutions provides important considerations necessary for inphase emission from a single output facet, the validity of this description is limited to continuous-wave (cw) emission for pump strengths very close to threshold.…”
Section: Introductionmentioning
confidence: 99%
“…In one depiction [9], the array of coupled lasers is treated as a single compound-cavity laser. The intrinsic laser dynamics are ignored and coherent beam combination is discussed in terms of the static eigenmodes, often referred to as supermodes, of the compound-cavity setup [18]. Although an analysis of these solutions provides important considerations necessary for inphase emission from a single output facet, the validity of this description is limited to continuous-wave (cw) emission for pump strengths very close to threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Passive phase locking employs optical coupling among lasers in either monolithic chip or external cavity. As a result, lasers oscillate in a collective coupled-mode pattern [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It was demonstrated that phases of chaotic lasers can be locked together due to optical coupling and optical coupling retains broad response bandwidth [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Proper optical coupling with strong collective mode discrimination is the key for a successful passive phase locking. External Talbot cavity imposes diffraction feedback coupling with strong collective mode discrimination and therefore was successfully utilized for coherent beam combining of single mode laser diode (LD) array [8,9,11]. The combined power was limited by the number of phase locked LDs and the power of each LD.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillation condition for a round trip (from the cavity facet of the laser array) can be described by [18,19] …”
Section: Device and Designmentioning
confidence: 99%
“… n (x) and  m (x) are described in [18]. P, the propagation matrix for the Talbot cavity, can be given by…”
Section: Device and Designmentioning
confidence: 99%